Strategic planning in Polish municipalities and the quadruple helix approach: An analysis of the relationship between local stakeholder involvement and strategy development methods - Dziemianowicz, Wojciech; Cybulska, Magdalena; Stokowski, Michał (Quaestiones Geographicae, 2026)
This article focuses on the tools used in the strategic planning process and the involvement of various stake-holder groups based on the results of a survey. A computer-assisted web interview (CAWI) survey was conducted for the purposes of this study. Of the responses received, 150 were used for the analysis in this article. The most commonly used methods for developing strategies within the study group are SWOT analysis, whilst the most popular techniques for gathering information are open and internal workshops, statistical data analysis and surveys. An attempt to verify three hypotheses indicates that the broad involvement of stakeholders (quadruple helix approach) favours the diversity of methods used, but it is still unknown whether it influences the use of the scenario approach. The analysis also did not confirm a statistically significant relationship between the size of the municipality and the use of advanced planning techniques. The results of the study indicate the need for further exploration of this subject area in order to clarify the basic relationships.